PENGEMBANGAN MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK DAN MEMBACABERBASIS MULTIMEDIA INTERAKTIF SISWA KELAS IV SEKOLAH DASAR - Maruti, Endang Sri (Premiere Educandum, 2015)
This research aims to develop interactive multimedia â based instructional mediain order to improve students listening and reading skills. This research refers to thedevelopment of 4-D method. 33 test subjects as children. Validation of researchinstruments are sheets, observation sheets, questionnaires, and learning tests. Datacollection techniques used validation and observation techniques. Techniques of dataanalysis used qualitative descriptive data. Lesson plan results demonstrate feasibility canbe trusted with a good reliability of the instrument category. The observation of studentactivity meets the criteria specified limits effectiveness. Based on the questionnaireresponses of students, learning with interactive CD was interesting. Student learning outcomes showed positive development. Thus, theproducts developed have been effective.Keywords: development, instructional media, listeningskills, readingskills, interactive multimedia